2019
DOI: 10.18203/2349-2902.isj20191270
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: correlation of receptor status with clinical presentation, stage of disease, histopathological grade and short term outcome

Abstract: Background: Breast cancer is the commonest female cancer representing a quarter of all cancers worldwide. An important development in breast cancer management was the realization of role of hormone receptors in disease. Thus, the present study was carried out to evaluate the receptor status and its correlation with clinical presentation, stage, grade and short term outcome.Methods: All female patients with lump in breast confirmed as breast cancer were included and their receptor status was evaluated using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Invasive ductal carcinoma, not otherwise specified (IDC-NOS), constituted the most predominant histological type, accounting for 124 (95.4%) cases (Figure 1 ). Similar results were documented in earlier reports, with IDC-NOS being the most common histologic type of breast cancer [ 2 , 7 , 10 - 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Invasive ductal carcinoma, not otherwise specified (IDC-NOS), constituted the most predominant histological type, accounting for 124 (95.4%) cases (Figure 1 ). Similar results were documented in earlier reports, with IDC-NOS being the most common histologic type of breast cancer [ 2 , 7 , 10 - 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, Grade III predominated with 66 (50.77%) cases while previous studies in neighboring regions showed Grade II as the most predominant grade [1,6,7,[10][11]. High-grade tumors were mostly negative for hormonal receptors, a finding consistent with that reported by Hashmi et al [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar data is reported by various local and international studies done so far where invasive ductal carcinoma was the most common type of breast cancer. 5,18,[24][25][26] TNM staging of the patients in the current study showed that 14.8% of cases were in stage IV of the disease. A study from Faisalabad showed that 21.7% of cases were in stage IV of the disease which is quite high compared to the figures in the current study.…”
Section: Discussionmentioning
confidence: 45%